CT-derived vessel segmentation for analysis of post-radiation therapy changes in vasculature and perfusion - Wuschner, Antonia E.; Flakus, Mattison J.; Wallat, Eric M.; Reinhardt, Joseph M.; Shanmuganayagam, Dhanansayan; Christensen, Gary E; Gerard, Sarah E.; Bayouth, John E. (Frontiers in Physiology, 2022)
Vessel segmentation in the lung is an ongoing challenge. While many methods have been able to successfully identify vessels in normal, healthy, lungs, these methods struggle in the presence of abnormalities. Following radiotherapy, these methods tend to identify regions of radiographic change due to post-RT toxicities as vasculature falsely. By combining texture analysis and existing vasculature and masking techniques, we have developed a novel vasculature segmentation workflow that improves specificity in irradiated lung while preserving the sensitivity of detection in the rest of the lung. Furthermore, radiation dose has been shown to cause vascular injury as well as reduce pulmonary function post-RT. This work shows the improvements our novel vascular segmentation method provides relative to existing methods. Additionally, we use this workflow to show a dose dependent radiation-induced change in vasculature which is correlated with previously measured perfusion changes (R$^2$=0.72) in both directly irradiated and indirectly damaged regions of perfusion. These results present an opportunity to extend non-contrast CT-derived models of functional change following radiation therapy.